Preeclampsia Is a Biomarker for Vascular Disease in Both Mother and Child: The Need for a Medical Alert System - Julie Hakim; Mary K. Senterman; Antoine M. Hakim (International Journal of Pediatrics)
This paper reviews the literature pertaining to the impact of preeclampsia not only on the mother but particularly on the children. The review points to the higher blood pressure in children born to preeclamptic mothers compared to controls, their increased tendency to suffer strokes, the reduction in their cognitive ability, and their vulnerability to depression. Mechanisms that may induce these changes are emphasized, particularly the placental vascular insufficiency and the resulting hypoxic and proinflammatory environments in which the fetus develops. The hypothesis proposed is that these changes in the fetal-placental environment result in epigenetic programming of the child towards a higher propensity for vascular disease. The review’s main recommendation is that, within ethical boundaries, the medical records of individuals born to preeclamptic mothers should clearly indicate this event and should be made available to the affected individuals so that preventive measures against vascular complications and lifestyle changes that may mitigate the latter can be instituted.